A COMPARATIVE STUDY OF YOGA AND STRUCTURED EXERCISES ON PAIN, MUSCLE PERFORMANCE, STRESS AND QUALITY OF LIFE IN PRIMARY DYSMENORRHEA - Shivani Ahuja; Ankit Yadav; Mansi Mittal; Jeyanthi S (Universitas Airlangga, 2025)
Introduction: With a prevalence of 25 to 90% in India, primary dysmenorrhea is a frequent ailment among women of reproductive age. Management of primary dysmenorrhea is selected from multidisciplinary options, which mainly consist of pharmacological intervention, but other alternative methods like yoga and exercise are also available. However, none of the researchers have compared the effects of yoga and exercise in primary dysmenorrhea. Aim: To compare the efficacy of yoga and structured exercises on pain, stress, quality of life and muscle performance in primary dysmenorrhea. Methods: Forty participants were randomly divided into two groups: one for yoga and the other for structured exercises. A total of twelve sessions were conducted over a period of three weeks. The baseline assessment was conducted on the 3rd day of the menstrual cycle, while the post-test was conducted on the 3rd day of the next consecutive cycle. After data acquisition, the results were analyzed using repeated measures ANOVA. Result: Following the intervention, both groups demonstrated significant improvement (p < 0.05). But changes were not statistically significant between the two groups. Conclusion: Both yoga and exercise were effective in reducing pain and stress, as well as improving quality of life and muscle performance in primary dysmenorrhea.